Communication between dentists and dental technicians in Lisbon for the construction of removable partial dentures' metal frameworks - Isabel Gomes; Filipa Reis; Teresa Mendes; Luís Pires Lopes (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2023)
Objectives: To evaluate the communication between dentists and dental technicians in Lisbon for the construction of metal frameworks for removable partial dentures (RPDs). Methods: This observational study's target population was laboratories in Lisbon. Data were collected through a questionnaire including six categories: medical prescription, conventional definitive impression and its disinfection, digital impression, analysis of study and working casts, and design and construction of the metallic structure. Dental technicians completed the questionnaire after consulting the medical instructions and observing the stone casts. The variables were subjected to descriptive statistics. Results: Three laboratories agreed to participate in this study, and the final sample included 53 entirely completed questionnaires. All definitive casts were obtained by conventional impression, with a universal tray (67.9%) and alginate (84.9%). The laboratories disinfected all impressions, mostly with sodium hypochlorite (98.1%), and the dental technician analyzed 84.9% of the casts in the parallelometer. There were no pre-prosthetic preparations in 66% of the working casts. The dentists provided design instructions in five cases, and only one delivered a drawing on paper. All metal frameworks were made in cobalt-chromium, mainly by electronic induction casting (96.6%). Conclusions: The dentist did not provide the dental technician with most of the design and planning instructions required for constructing removable partial dentures. This finding confirms the lack of communication between clinics and laboratories in Lisbon.